The eclectic landscape: examining Spanish secondary school teachers’ beliefs on literary education - Fabregat-Barrios, Santiago; Fontich, Xavier; González-González-de-Mesa, Carmen (Frontiers in Education, 2023)
Literary education aims to promote the teaching of reading from an academic, social, and personal perspective. At present there is a consensus on the central role that the school institution plays, which can be translated into explicit and implicit approaches. The objective of this article is to explore Spanish Secondary school teachers' beliefs about literary education to determine their proximity to each of these two approaches, as well as the coherence within such beliefs, unpacking the relationships between adherence to principles and declared practices. To obtain the data that supports the study, the Beliefs About Literary Education of Secondary School Teachers (BALESST) scale has been elaborated. 1,544 Secondary Education teachers from the 17 Spanish communities and the autonomous cities of Ceuta and Melilla have responded to the scale. For the analysis of the data, the statistical packages of IBM SPSS Statistics, 24.0 and G* Power 3 have been used. The results suggest that Spanish Secondary school teachers are in an eclectic position in the debate between explicit and implicit literary education, reveal relevant discrepancies between the two factors that make up the scale (adherence to principles and declared practices), and allow identify majority and minority representations and practices among teachers.